Adsorption behavior of drugs on hydroxyapatite with different morphologies: A combined experimental and molecular dynamics simulation study. Issue 15 (15th October 2019) - Zhao, Qing; Zhang, Dongqing; Sun, Ruixue; Shang, Shengcong; Wang, Huachun; Yang, Yuyao; Wang, Lian; Liu, Xiaokun; Sun, Tianxiang; Chen, Kezheng
Abstract: Hydroxyapatite (HAp) with dual functions of focus filling and drug sustained release plays an important role in the treatment of many bone diseases. In this study, HAp with two different morphologies (hollow microsphere and nanoparticle) were fabricated by a simple hydrothermal method. Compared with the nanoparticle, the hollow microsphere of HAp exhibited higher loading efficiency and sustained release of doxorubicin for a longer time. However, for tinidazole, both nanoparticle and hollow microsphere of HAp showed low drug loading efficiency. The molecular dynamics simulation results proved that the binding energy of doxorubicin on HAp was much higher than that observed for tinidazole. The amount and activity of "O" atoms in the drug molecule affect the adsorption efficiency of drugs on HAp. Therefore, the main factors affecting the adsorption efficiency of HAp are the chemical structure of the drug itself, followed by the specific surface area and pore structure of HAp. Overall, this comprehensive study offers new insights into the understanding of drug adsorption on HAp.